Impact of the CAP on Archaeological Heritage. Cause & Remedy? - Cordemans, Karl; Byrnes, Emmet; van Rooijen, Cees (Ex Novo: Journal of Archaeology, 2019)
This paper seeks to summarise the origin and evolution of the Common Agricultural Policy (CAP) in terms of the impact its policies and measures have had - and continue to have - on archaeological features and sites situated on arable land. The effects have been very obvious in some cases, less visible in others, but invariably significant. At the same time, the European policy on agriculture and rural development, and the Treaty provisions for the CAP can also present solutions and mitigation measures for the problems. Some examples will be presented within this paper, along with a forecast for the next programming period (2021-2027). The authors are members of the EAA and EAC working group on Farming, Forestry and Rural Land Management. One of the aims of this working group is to improve the management of archaeological heritage in those areas.